Ode to Field Geology of Williams: Fleur de Lys Nectar Still Fermenting on Belle Isle - de Wit, Maarten; Armstrong, Richard (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2014)
Throughout the 1960s, Hank Williams put Newfoundland on the proverbial global map as one of the most complete cross-sections of the Appalachian Orogen, and he became a champion attractor to this unique geological laboratory. By the end of the 1960s, Williams, together with Bob Stevens, had mapped the rocks of Belle Isle in the treacherous waters north of the Long Range Peninsula, and suggested their siliciclastic rocks were equivalent to those of the Fleur de Lys type sections on the Burlington Peninsula some 200 km away across White Bay, and by implication that the underlying Laurentian basement on Belle Isle should have its counterpart there too. New U–Pb geochronology on zircon from two samples of possible basement to the Fleur de Lys Supergroup is presented here. These data verify unequivocally the wisdom of the original suggestions based on dedicated field work. The new data also provide evidence that by the earliest Ordovician (ca. 483 Ma), high pressure-low temperature metamorphism at depths in excess of 30 km occurred in Fleur de Lys Supergroup domains. The tectonic implications of these findings are explored, and from this it emerges that only new mapping integrated with high-resolution geochronology and thermochronology are required, both on Belle Isle and in the Fleur de Lys Supergroup, to advance beyond the standards set by Hank Williams.